Rise of the Evening Star : Fablehaven #2 - Mull, Brandon ([Salt Lake City, Utah] : Shadow Mountain, 2007)
At the end of the school year, Kendra and Seth find themselves racing back to Fablehaven, the refuge for mythical and magical creatures. Grandpa Sorenson, the caretaker, invites three specialists - a potion master, a magical relics collector, and a mystical creature trapper - to help protect the property from the Society of the Evening Star, an ancient organization determined to infiltrate the preserve and steal a hidden artifact of great power. With Evening Star storming the very gates of Fablehaven, will Kendra learn to use her fairy gifts in time?
Keywords: Magic -- Fiction; Grandparents -- Fiction; Brothers and sisters -- Fiction; Magical creatures -- Fiction